Early screening and treatment of gestational diabetes in high-risk women improves maternal and neonatal outcomes: A retrospective clinical audit. (October 2018) - Ryan, David K.; Haddow, Laura; Ramaesh, Aksha; Kelly, Rod; Johns, Emma C.; Denison, Fiona C.; Dover, Anna R.; Reynolds, Rebecca M.
Highlights: Evidence suggests that current GDM screening occurs too late in pregnancy. There is no consensus as to the management of early pregnancy GDM. We introduced a protocol encouraging the earlier identification and treatment of GDM. Such a protocol improved pregnancy outcomes compared to routine screening. This suggests a role for early GDM screening and interventions in early pregnancy. Abstract: Aims: Evidence suggests that screening for gestational diabetes (GDM) occurs too late in pregnancy, when changes in glucose metabolism and fetal growth rates can already be detected. In August 2016 NHS Lothian began screening women with risk factors for GDM during early pregnancy (11–13 weeks). We hypothesised that an earlier identification and treatment of dysglycaemia would improve pregnancy outcomes compared to previous standard care. Methods: We compared management and outcomes for singleton pregnancies with GDM delivering at Royal Infirmary Edinburgh, UK, diagnosed through routine or early screening from 01/01/2015–31/10/2017 (routine screening n = 335, early screening n = 241). Results: Early screening increased the proportion of women diagnosed before 24 weeks' gestation (n = 59/335, 17.6% vs n = 103/241, 42.7%, p < 0.001) but did not change the average monthly rate of diagnosis. Early screening increased the median duration of GDM during pregnancy (71 vs 93 days of gestation, p < 0.001) with no significant changes in the pharmacological management. Early screening improved the primary composite outcome (emergency caesarean section, neonatal hypoglycaemia and macrosomia; n = 138/335, 41.2% vs n = 73/241, 30.3%, adjusted Odds Ratio [95% confidence interval] 0.62 [0.43–0.91]. Conclusions: There is a role for early screening and management of GDM however it is unclear whether this represents a cost-effective intervention.